Implementation of the Value of Moderation in Education: Study of Term al-Wasath in Surah al-Baqarah verse 143 with Abdullah Saeed's Contextual Hermeneutics Approach - Nurjannah, Nurjannah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
This study aims to determine the implementation of the value of moderation contained in QS Al-Baqarah verse 143 in the world of education. The moderation value is obtained from a study of the meaning of al-wasath contained in the verse. The study was conducted using the term thematic method with the Contextual Hermeneutics approach initiated by Abdullah Saeed. Namely, capturing the messages and teachings of the Qur'an by considering the historical context of the text and the historical context of the application of the text. This study found that, 1) the meaning of the term al-wasath is a state in the middle, in worldview and life in the hereafter and physical and spiritual behavior, not to act in extreme and radical ways, 2) historically, term al-wasath in QS al -Baqarah: 143 is used to express the moderate attitude of a farmer who thinks well of the crop failure he has experienced, and in context this term shows a tolerant attitude towards various differences that occur in life, 3) the application of moderation values in education can be done with several approaches, namely the value instilling approach, the cognitive moral development approach, the value analysis approach, the value clarification approach, and the learning to do approach. Through this approach, moderate attitudes are instilled which can give birth to tolerance, mutual respect and compassion among people. 3) the application of moderation values in education can be carried out using several approaches, namely the value instilling approach, the cognitive moral development approach, the value analysis approach, the value clarification approach, and the learning to do approach. Through this approach, moderate attitudes are instilled which can give birth to tolerance, mutual respect and compassion among people. 3) the application of moderation values in education can be carried out using several approaches, namely the value instilling approach, the cognitive moral development approach, the value analysis approach, the value clarification approach, and the learning to do approach. Through this approach, moderate attitudes are instilled which can lead to tolerance, mutual respect and compassion among people